Pleural Fluid Cytokine Levels at Baseline and Over Time are Associated With Time to IPC Removal: An Exploratory Study. Issue 1 (January 2020) - Grosu, Horiana B.; Lu, Wei; Ost, David E.; Vial, Macarena R.; Hernandez, Mike; Ghosh, Natasha; Noor, Laila; Hasan, Arain M.; Bashoura, Lara; Faiz, Saadia; Balachandran, Dave; Casal, Roberto; et al.
Abstract : Background: The behavior of pleural fluid cytokine (PFCs) levels and their association with pleurodesis after indwelling pleural catheter (IPC) placement is unknown. Objective: A prospective exploratory study was conducted to obtain preliminary data on PFC levels after IPC placement. Methods: The PFC panel consisted of 4 cytokines [interleukin -8 (IL-8), vascular endothelial growth factor, total (but not activated) transforming growth factor betas, and basic fibroblast growth factor], measured across 5 time points (T0: insertion; T1: 24 to 48 h; T2: 72 to 96 h; T3: 1 wk; and T4: 2 wk). Profile plots were used to identify patterns of change of PFC levels. Correlation matrices for each PFC over time were computed, and area under the curve (AUC) categories were used to compare the cumulative incidence of IPC removal. Auto pleurodesis was defined as elective catheter removal because of decreased drainage within 90 days of insertion. Results: A total of 22 patients provided complete data. Except for IL-8, the majority of PFCs demonstrated strong positive correlations across measurement time points. Patients with high AUCs for IL-8, basic fibroblast growth factor, and vascular endothelial growth factor had a higher cumulative incidence of IPC removal by 90 days than did patients with low AUCs. Conclusion: This is the first study to evaluate longitudinal changes of pleural cytokine levels with respect to the likelihood of IPC removal and provide early evidence that the cytokine profile may be associated with the outcome of pleurodesis induced by IPCs. However, this is an exploratory study and further studies are needed to assess if these findings can be validated in further studies. Abstract : Supplemental Digital Content is available in the text.